FACTORS INFLUENCING THE UTILISATION OF AGRICULTURAL INFORMATION AMONG ARABLE CROP FARMERS IN BORNO STATE, NIGERIA - Gadzama, A. A.; Ndaghu, A. A.; Tafida, A. A.; Barazi, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing the utilization of agricultural information among arable crop farmers in Borno State, Nigeria. This study specifically examined farmers identified major sources of information, examined socio-economic factors influencing these dynamics among arable crop farmers and identified the barriers hindering effective use. Multistage sampling procedure was employed to select 387 respondents. Data were collected using a structured questionnaire and analysed using descriptive statistics and ordinal logistic regression. Findings indicated that, the most commonly used sources of information were informal, such as fellow farmers (54.9%) and radio (55.7%), while institutional sources remained underutilized. Ordinal logistic regression analysis revealed that utilization of agricultural information was significantly influenced by education level (β = 0.2536), access to credit (β = 0.8215), income (β = 0.0000192) and farm size (β = 0.1487), all statistically significant at the 5% level. Major constraints identified included high costs associated with accessing information (64.8%), irregular extension contact (62.4%), low literacy levels (59.7%) and language barriers (54.3%). The study concludes that education level, accessed to credit, income, farm size, social participation and extension contact were the factors influencing the utilization of agricultural information among arable crop farmers in the study area. It is recommended that government agencies and stakeholders strengthen agricultural extension systems, improve rural ICT infrastructure, provide targeted funding support, and implement farmer-centered training programs to enhance information access and utilization.